Efficiency measurement of the citrus extractor prototype - Salvador, Lualhati Q.
Efficiency of the citrus extractor prototype was measured relative to hand-reaming in terms of process parameters and product quality factors during the two-week storage period. Process parameters determined include extraction time, efficiency coefficient, ratio of broken seeds to whole seeds, % yield, and % loss. Product quality was evaluated in terms of sensory attributes and physico-chemical characteristics. Optimum load and kalamansi sizes for mechanical extraction were also determined to obtain maximum efficiency from the citrus extractor. Fruit maturity utilized was chosen on the basis of highest % yield obtained from different levels of maturity. Based on results obtained, mechanical extraction appears to be a better extraction method than hand-reaming in terms of reduction in extraction time and ration of broke seeds to while seeds and increase in efficiency coefficient. However, higher yield and lower loss were obtained for hand reaming. No significant difference between samples were observed by panelists on the 14th day of storage. Maximum efficiency from the citrus extractor was obtained when stem and apex ends of the fruits are cut away before introduction to the machine to a load of 8 kg. Maximum yield by mechanical extraction was 22.6% obtained from fruits with a diameter ranging from 28.5-32 mm. Fruits which are soft to those which are firm and slightly softy and colored yellow to green with yellow spots were observed to provide maximum juice yield by hand-reaming. With minor modifications and adjustments in machine design, mechanical extraction using the citrus extractor may prove to be a better extraction method than hand-reaming as a time and labor saving method and capable of providing a product comparable to hand-reaming. Operation procedure based on results should be maintained to maximize efficiency and output of the citrus extractor. Like any machine equipment, maximum utility is determined by proper care and maintenance over the citrus extractor.